[Roman Catholic Cathedral, Trinidad, B.W.I.] - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Photo of Roman Catholic Cathedral, "Cathedral of the Immaculate Conception" in Port of Spain, Trinidad and Tobago. This Cathedral was built on the site west of Tamarind Square, where the first Catholic church ever built in Port of Spain was erected of wood and clay in 1781. The foundation stone for the Cathedral of the Immaculate Conception was laid in March 1816 on the eastern end of what was then known as Marine Square, now Independence Square. The church was consecrated Palm Sunday 15 April 1832, completed in 1936 and in 1851 was ranked a Minor Basilica. Twelve bells and a clock were added in 1879. Built in Gothic design in the shape of a Latin Cross, the walls and two grand towers that flank the entrance were made of blue limestone mined from the Laventille quarries. The towers however had to be replaced after they were destroyed in an earthquake 1825. One of the unique features of the Cathedral is a crypt beneath the building that houses the final remains of Catholic Church officials, including Archbishops interred here from 1828 to 2000.
Colour: White, Grey and Black Hues; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Christianity--Trinidad and Tobago; Catholics--Trinidad and Tobago; [1900]; Catholic church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago; Architecture--Details; Cathedrals--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Clocks and watches--Trinidad and Tobago; Towers--Trinidad and Tobago; Shrubs--Trinidad and Tobago; Gates--Trinidad and Tobago; Fences--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)